P200 ISCHEMIC HEART IN PAZIENTS UNDER 30: AN UNSOLVED CHELLENGE. (18th May 2022) - Annalisa, F; Trotta, R; Pollicino, T; Abbracciavento, L; Luzzi, G
Abstract: Background: The pathogenesis of ischemic heart disease (IHD) in young patients is still unclear. Several studies have demonstrated the existence of peculiar cardiovascular risk factors (CRFs) that differ from the typical factors involved in the more common IHD of adults.Plaque rupture represents the most common etiology of myocardial infarction (MI), nonetheless, other events can play a role in young patients affected by IHD, including coronary artery plaque erosion, coronary microvascular dysfunction, spontaneous dissection of the coronary artery, and coronary artery spasm secondary to drug abuse. Due to the differences in the clinical manifestations, diagnosis, and therapeutic management, further research is needed to study the profile of MI in young patients1 Clinical Case: A 28–year–old male, occasional smoker, negative familiar anamnesis for IHD. His past medical history was significant for an acute coronary syndrome (ACS) STEMI at the age of 20 years old, treated with percutaneous transluminal coronary angioplasty (PTCA) with scaffold in the interventricular anterior artery (IVA). After 7 years he was admitted following a thrombotic occlusion of the IVA, managed with PTCA/ drug–eluting stent (DES) followed by coronary artery bypass surgery diverting the blood flow of the IVA in the left internal mammary artery (IMA). After only 11 months he presented with a new ACS NSTEMI treated with PTCA/DES of the IVA in the left IMA. No biochemical signs of coagulopathy or peripheral artery disease were disclosed, and the supra–aortic trunks resulted normal. Nevertheless, a significant increase in the blood levels of homocysteine and slightly elevated values of fibrinogen, D–dimers, and C–reactive protein. Erythrocyte sedimentation rate resulted within the physiological ranges. Discussion and Conclusion: The peculiar medical history of the described patient suggests a marked tendency not only for the formation and plaque rupture but also for platelet aggregation. The only significant and persistent values that were found to be elevated were homocysteine and inflammatory markers. One–year follow–up examination revealed complete regression of the symptoms with double antiaggregating therapy and supplements of folic acid. The rarity of such cases should prompt new research to better understand IHD in this population and possible targeted treatments Acute Myocardial Infarction in Young Individuals; Rajiv Gulati; Mayo Clinic Proceedings, V 95, I. 1, P136–156, 2020.